Potential paths to Canada's climate commitments through strategic solar photovoltaic deployment - Shafquat Rana; JoshuaM. Pearce (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
Canadian climate policy calling for a transition to renewable energy is not only a response to the increasing frequency and liability of climate-related disasters, but also a strategic move to mitigate fossil-fuel economic volatility. The easiest path to transition is using the lowest-cost source of energy, which is solar photovoltaics (PV). This study brings clarity to Canada’s efforts to achieve the net zero target quantifying growth rates of PV system development required to reach net zero. First, Canada’s net energy goal background and the recent solar PV-specific growth, markets, and policies are reviewed. Next, the methodology for achieving Canada’s climate goal with PV deployment is detailed. The results indicate to meet carbon emissions targets in 2030 (40 % and 45 % below 2005) and be net-zero by 2050 requires 666, 762, and 1847 GW of PV, respectively. The latter solar PV required increases to 2019 GW with the expected 7.5 % escalation in primary energy. The 2023 total PV capacity installed in Canada is 4.6 GW and the rate of growth is completely inadequate to achieve Canada’s goals. This study presents different approaches to achieve Canada’s emissions goals using PV and details deployment in terms of energy, investment, and employment pointing towards the need of new policies.